Sertifikasi Halal sebagai Instrumen Kebijakan Publik dalam Pengembangan Industri Halal Indonesia - Sunarta, Desy Arum; Bulqis, Rasyidah; Bisyriani, Andi; Sudirman, Muh. Sajjaj; Apriliani, Riski (IAIN Kendari, 2025)
This article presents a literature synthesis on the role, challenges, and opportunities in the development of halal certification within the Islamic economic framework. Halal certification functions not only as religious compliance but also as a strategic tool to enhance product competitiveness, ensure quality, and build consumer trust. Nevertheless, its implementation still encounters various obstacles, such as bureaucratic complexity, limited halal literacy, and unequal access, especially for small and medium enterprises. Despite these challenges, significant opportunities lie ahead, particularly in the digitalization of certification systems, expansion into the cosmetics, pharmaceutical, and halal tourism sectors, and the strengthening of international cooperation. This study highlights the importance of collaborative efforts among government, industry, and academia to develop an inclusive and efficient halal certification system. A well-integrated and adaptive certification mechanism has the potential to become a major driver for national Islamic economic growth and to strengthen Indonesia’s position in the global halal market